Pengaruh Pengawasan Preventif, Pengawasan Detektif, dan Implementasi Strategi terhadap Efektifitas Pengendalian Anggaran - Muhammad Fakhrul Muttaqien; I Gusti Ketut Agung Ulupui; Muhammad Yusuf (Jurnal Akuntansi, Perpajakan dan Auditing, 2026)
This study aims to determine the effect of Preventive Supervision, Detective Supervision and Strategy Implementation on the Effectiveness of Budget Control. This study uses primary data with the respondents being employees who are directly responsible for the preparation and absorption of the budget at the South Jakarta Mayor's Office. The population in this study was sampled using a saturated sampling technique. The number of respondents as many as 60 respondents. The data were tested using multiple regression models using the SPSS 25 application. The results of this study indicate that detective supervision and strategy implementation have a significant effect on the effectiveness of budget control, while preventive supervision has no effect on the effectiveness of budget control. It is hoped that further research will add or use other variables to test the effectiveness of budget control. In addition, increasing the sample by examining more than one mayor's office, in order to be able to examine more deeply the effectiveness of budget control, preventive supervision, detective supervision and strategy implementation in public sector accounting.